2014
DOI: 10.1371/journal.pone.0106105
|View full text |Cite
|
Sign up to set email alerts
|

A Further Investigation of Combined Mismatch Repair and BRAFV600E Mutation Specific Immunohistochemistry as a Predictor of Overall Survival in Colorectal Carcinoma

Abstract: Mutation specific immunohistochemistry (IHC) is a promising new technique to detect the presence of the BRAFV600E mutation in colorectal carcinoma (CRC). When performed in conjunction with mismatch repair (MMR) IHC, BRAFV600E IHC can help to further triage genetic testing for Lynch Syndrome. In a cohort of 1426 patients undergoing surgery from 2004 to 2009 we recently demonstrated that the combination of MMR and BRAFV600E IHC holds promise as a prognostic marker in CRC, particularly because of its ability to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Of the studies that included patients with stage I through IV MSI CRC (Supporting Information Table ) only one reported BRAF to be significantly prognostic . Studies specifically on metastatic CRC have related the presence of BRAF mutation with worse survival within the MSI subset of CRC …”
Section: Discussionmentioning
confidence: 99%
“…Of the studies that included patients with stage I through IV MSI CRC (Supporting Information Table ) only one reported BRAF to be significantly prognostic . Studies specifically on metastatic CRC have related the presence of BRAF mutation with worse survival within the MSI subset of CRC …”
Section: Discussionmentioning
confidence: 99%
“…7,21 Negative staining (MMRd/MSI) was defined as completely absent nuclear staining in the neoplastic cells in the presence of a positive internal control (Figure 1), while the MMRp/MSS pattern was defined by positive nuclear staining for all four markers in neoplastic cells (Figure 2). In our hands, we have previously demonstrated excellent concordance between immunohistochemistry interpreted on tissue microarrays and whole sections, 18 and if there was uncertainty about interpretation of the immunohistochemistry, stains were repeated on whole sections.…”
Section: Methodsmentioning
confidence: 99%
“…5) and 42% 6 of mucinous colorectal cancers have been reported to demonstrate MSI/MMRd compared with 20% or less of all unselected colorectal cancers. 7 Although some studies have reported worse survival outcomes and poorer response to chemotherapy in mucinous colorectal cancer, 8,9 to date findings have been inconsistent, with some studies showing no mortality association with mucinous histology. [10][11][12] Pathological grading of mucinous CRC is problematic.…”
mentioning
confidence: 99%
“…In metastatic CRC, KRAS, NRAS and BRAF genes have already been the conventional testing indexes . Combined KRAS/BRAF‐MMR status was suggested to be prognostic for CRC outcomes in several studies . In stage II‐III CRC, a poorer survival was observed for pMMR patients with KRAS/BRAF mutations compared with wild‐type ones, while KRAS/BRAF mutations seemed to have no impact on survival outcomes for dMMR patients .…”
Section: Discussionmentioning
confidence: 99%